Lectotypification of Lophopogon kingii (Poaceae, Andropogoneae) - Tiwari, Arjun Prasad; Gavade, Sandip; Mujaffar, Shaikh (Phytotaxa, 2017)
The genus Lophopogon Hackel (1887: 26) is endemic to India (Singh et al. 2015) and consist of two species: L. tridentatus (Roxburgh 1820: 261) Hackel in Candolle & Candolle (1889: 26) and L. kingii Hooker (1896: 149). The latter species is known from the type locality in Monghyr district of Bihar state and recently recorded from Satkosia Tiger Reserve in Odisha state (Chandramohan et al. 2016). During the taxonomic study of L. kingii Hook.f., the name resulted not yet typified.